Sortase-encoding genes, srtA and srtC, mediate Enterococcus faecalis OG1RF persistence in the Helicoverpa zea gastrointestinal tract - Jackson, Jerreme J.; Heyer, Samantha; Bell, Geneva (Frontiers in Microbiology, 2024)
Enterococcus faecalis is a commensal and opportunistic pathogen in the gastrointestinal (GI) tract of mammals and insects. To investigate mechanisms of bacterial persistence in the gastrointestinal tract, we developed a non-destructive sampling model using the Helicoverpa zea, a destructive agricultural pest, as host to study the role of bacterial sortase enzymes in mitigating persistence in the gastrointestinal tract. E. faecalis OG1RF srtA and E. faecalis OG1RF srtC, isogenic E. faecalis OG1RF sortase mutants grew similarly under planktonic growth conditions relative to a streptomycin-resistant E. faecalis OG1RFS WT in vitro but displayed impaired biofilm formation under, both, physiological and alkaline conditions. In the H. zea GI model, both mutants displayed impaired persistence relative to the WT. This represents one of the initial reports in which a non-destructive insect model has been used to characterize mechanisms of bacterial persistence in the Lepidopteran midgut and, furthermore, sheds light on new molecular mechanisms employed by diverse microorganisms to associate with invertebrate hosts.